Review of the Pathogenesis and Classical Formula of Ulcerative Colitis in Traditional Chinese Medicine - Chen, Zhen; Ma, Chengyan; Zhang, Wei; Wang, Hongwei; Yu, Tao (Journal of Contemporary Medical Practice, 2025)
Ulcerative Colitis (Ulcerative Colitis, UC) is a chronic nonspecific inflammatory bowel disease with complex etiology and prone to recurrent episodes, significantly impacting patients’ quality of life. Although traditional Chinese medicine does not have a specific name for this condition, it categorizes it under conditions such as “dysentery,” “diarrhea,” and “intestinal inflammation.” This article begins with an analysis of the etiological and pathogenic mechanisms of UC from the perspective of traditional Chinese medicine, systematically examining common TCM syndromes. It focuses on the therapeutic characteristics of classic formulas like Shen Ling Bai Zhu San, Taohua Tang, Bai Tou Weng Tang, Si Shen Wan, and Bu Zhong Yi Qi Tang in different syndromes, along with their modern pharmacological research foundations. The article also explores their multi-target mechanisms in regulating immune function, repairing intestinal barriers, and maintaining microbial balance. Additionally, it summarizes the advantages and current limitations of TCM in treating UC, aiming to provide theoretical basis and reference for future clinical diagnosis and research.